Clinical and preclinical insights into a novel MDM2::PDGFRA fusion in recurrent glioblastoma - Catherine Z. Beach; Christopher A. Febres-Aldana; Juan Luis Gomez Marti; Saeed Asiry; Tamika Wong; John A. Boockvar; Randy S. D’Amico; Romel Somwar; Monika A. Davare; Morana Vojnic (npj Precision Oncology)
Abstract Glioblastoma is an aggressive and treatment-refractory primary brain tumor with limited therapeutic options and high recurrence. The molecular heterogeneity of glioblastoma poses a significant challenge to therapeutic development, as targeted therapies have mostly failed in small-scale clinical trials, underscoring the need for comprehensive next-generation sequencing (NGS) characterization to identify mechanisms of resistance. In this study, we identify and functionally characterize a novel amplified fusion, MDM2 (exon 1)::PDGFRA (exon 8), mediating resistance to cetuximab in an EGFR-amplified glioblastoma. The fusion results in a truncated PDGFRA isoform, in vitro assays demonstrate that MDM2::PDGFRA acts as a constitutively active oncogenic driver with a distinct sensitivity profile to tyrosine kinase inhibitors. Analysis of a glioblastoma cohort indicates PDGFRA structural variants often co-occur with amplification and may serve as biomarkers. These findings highlight the importance of repeat NGS profiling in clinical management and provide a translational framework for identifying and targeting emergent fusion-driven alterations.